Imaging surveillance for complications after primary surgery for type A aortic dissection. Issue 2 (23rd March 2022) - Heuts, Samuel; Schalla, Simon; Ramaekers, Mitch J F G; Bidar, Elham; Mihl, Casper; Wildberger, Joachim E; Adriaans, Bouke P
Abstract : Acute type A aortic dissection (ATAAD) is a life-threatening condition that requires emergency surgery to avert fatal outcome. Conventional surgical procedures comprise excision of the entry tear and replacement of the proximal aorta with a synthetic vascular graft. In patients with DeBakey type I dissection, this approach leaves a chronically dissected distal aorta, putting them at risk for progressive dilatation, dissection propagation and aortic rupture. Therefore, ATAAD survivors should undergo serial imaging for evaluation of the aortic valve, proximal and distal anastomoses, and the aortic segments beyond the distal anastomosis. The current narrative review aims to describe potential complications in the early and late phases after ATAAD surgery, with focus on their specific imaging findings.